Altered miRNA expression profiling in enamel organ of fluoride affected rat embryos - Qingqing Weng; Fangyu Yi; Ying Yu; Suyu Ge; Shangfeng Liu; Ying Zhang (Ecotoxicology and Environmental Safety, 2021)
Evidence has shown that miRNAs could play a role in dental fluorosis, but there is no study has investigated the global expression miRNA profiles of fluoride-exposed enamel organ. In this study, we analysed the differentially expressed (DE) miRNAs between fluoride-treated and control enamel organ for the first time and found several candidate miRNAs and signaling pathways worthy of further research. Thirty Wistar rats were randomly distributed into three groups and exposed to drinking water with different fluoride contents for 10 weeks and during the gestation. The three groups were a control group (distilled water), medium fluoride group (75 mg/L NaF), and high fluoride group (150 mg/L NaF). On the embryonic day 19.5, the mandible was dissected for histological analysis, and the enamel organ of the mandibular first molar tooth germ was collected for miRNA sequencing (miRNA-seq) and quantitative real-time PCR analysis (qRT-PCR). Typical dental fluorosis was observed in the incisors of the prepregnant rats. In addition to the disorganized structure of enamel organ cells, 39 DE miRNAs were identiﬁed in the ﬂuoride groups compared with the control group, and good agreement between the miRNA-seq data and qRT-PCR data was found. The functional annotation of the target genes of 39 DE miRNAs showed significant enrichment in metabolic process, cell differentiation, calcium signaling pathway, and mitogen-activated protein kinase(MAPK) signaling pathway terms. This study provides a theoretical reference for an extensive understanding of the mechanism of fluorosis and potential valuable miRNAs as therapeutic targets in fluorosis.